Overwhelmed by family, but supported by likeminded, trustworthy coworkers: Effects on role ambiguity and championing behaviors - De Clercq, D.; Pereira, R. (Journal of Organizational Effectiveness: People and Performance, 2022)
Purpose This study addresses how and when the experience of family-induced work strain might steer employees away from efforts to promote innovative ideas. In particular, it proposes a mediating role of role ambiguity and moderating roles of two coworker resources (goal congruence and goodwill trust) in this process. Design/methodology/approach The research hypotheses are tested with data obtained from a survey administered among employees who work in a professional services organization. Findings An important explanatory mechanism that links family interference with work to diminished championing efforts is that employees hold beliefs that their job roles are unclear. The extent to which employees share work-related mindsets with coworkers, as well as their belief that coworkers are trustworthy, attenuate this harmful effect. Practical implications For HR managers, the study shows a clear danger that threatens employees who feel drained by significant family demands: The negative situation may escalate into work-related complacency (diminished championing), which then may generate even more hardships. As it also reveals though, employees can leverage high-quality coworker relationships to contain this danger. Originality/value This study adds to HR management research by investigating the role of negative spillovers from family to work in predicting idea championing, as explained by negative beliefs about job-related information deficiencies but buffered by high-quality coworker relationships.